Relationship of smartphone dependence with personal states and properties - Sheinov, Viktor P. (Journal of the Belarusian State University. Sociology, 2020)
Numerous studies show that smartphone addiction has a detrimental effect on many important aspects of modern life. The purpose of this article is an analytical review of foreign studies on the relationship between smartphone addiction and psychological states and personality traits. The adverse effects of excessive use of smartphones for physical and mental health were found in the form of depression, anxiety, stress, negative emotions, insomnia, poor sleep quality, and low physical activity. Excessive smartphone use predicts low self-regulation and poor self-control. Excessive smartphone communication makes people less empathetic to each other, resulting in a loss of empathy and a deterioration in emotional connection with others. Smartphone addiction is positively associated with attention deficit disorder, hyperactivity disorder, compulsive behaviour, and procrastination. Smartphone addiction to social media is linked to interpersonal issues and contributes to non-assertive behaviour and exposure to cyberbullying. The most active smartphone users receive the highest scores for addictive behaviour. Of the personality traits of individuals, loneliness and shyness are the strongest predictors of smartphone addiction. Smartphone addiction negatively affects communication skills. Unmarried people are more dependent on the smartphone. Women are more dependent on smartphones than men.